AB0967 Auto-Inflammatory Diseases Are a Main Cause of Early-Onset Panniculitis. (9th June 2015) - Bader-Meunier, B.; Melki, I.; Touzot, F.; Casanova, J.-L.; Neven, B.; Quartier, P.; Wouters, C.; Fraitag, S.; Bodemer, C.
Abstract : Background: Childhood-onset panniculitides are rare and classically include infectious, connective tissue, malignant, metabolic, and drugs, cold or trauma-induced panniculitis. Some specific types of panniculitis are only seen in neonates and very young infants, and include subcutaneous fat of the newborn, poststeroid panniculitis, sclerema neonatorum, and cold panniculitis. However, no specific discoverable etiology can be identified in many patients. Objectives: To describe the spectrum of clinical and pathological manifestations of childhood-onset panniculitis of unknown cause Methods: A retrospective single-center study of children presenting with panniculitis diagnosed by skin biopsy Results: Eighteen patients were identified. The onset of symptoms occurred within the first two years of life in 15/18 patients (83%). Panniculitis was the revealing manifestation in 15/18 (83%) patients, and relapsed in 13/18 (72%) patients. Associated-non-cutaneous features occurred in 16/18 (89%) patients, especially autoinflammatory manifestations in 13/18 patients (72%), associated with immunodeficiency in 5 patients (low T or B cells count with hypogammaglobulinemia in 4 and 1 patients respectively). Autoinflammatory manifestations consisted in attacks of fever with an elevation of acute phase reactants associated with polyarthritis or polyarthralgia (2 patients), rash (2 patients) or aseptic adenitis (2 patients). Panniculitis was mostly lobular in 10 (55%) patients, septal in 3 (17%) patients or both in 5 patients (28%). Predominant infiltrate consisted of neutrophils, cytophagic histiocytes, lymphocytes, eosinophils in 8 (44%), 5 (28%), 3 (17%), and 1 (5.5%) patients respectively, and included granuloma in 1 patient. No relationship was found between clinical and pathological features. Genomic mutations were identified in 3 of the 4 patients who underwent genetic analysis: mutations in TRNT1, MVK (mevalonate kinase) and LCK genes. Conclusions: This series underlines that auto-inflammatory diseases, possibly associated with inherited immunodeficiency, are a main cause of early-onset panniculitis. The identification of a monogenic cause in 3 patients and the early-onset presentation of the disease suggest that a subset of patients has a genetic predisposition to develop panniculitis, especially early-onset panniculitis. Disclosure of Interest: None declared